HOW PARENTING AFFECTS ADOLESCENT SELF-CONFIDENCE - Sarlina Sari (CV. Bunda Ratu, 2023)
This journal aims to analyze the relationship between parenting styles and the development of self-confidence in adolescents. Self-confidence is a crucial factor in individual development, particulary during adolescence, which is a transitional period filled with challenges. The parenting styles provided by parents and the surrounding environment can significantly impact adolescent’s social and emotional development, including their level of self- confidence. In this journal, a review is conducted on various theories of adolescents development, parenting styles, and relevant previous research. The analysis result indicate a connection between parenting styles and the development of adolescents self-confidence. Authoritative parenting, which combine responsiveness with clear boundaries, tends to be associated with positive self-confidence development. On the other hand, authoritarian or permissive parenting styles might have negative impacts on adolescents sel-confidence. Furthermore, factors such as parent-adolescents communication, emotional support, and parental role modeling also play crucial roles in shaping adolescents; self-confidence levels. The findings from this journal hold significant impications for enhancing the quality of parent-adolescent relationships and supporting positive self-confidence development in adolescents. Further research can delve deeper into understanding the mechanisms and variables involved in the interaction between parenting styles and adolescent self-confidence development.